The UME on X/Twitter: strategic communication and national security in the forest fires of 2025 - Rodríguez Hernández, Jonattan; Ortega Fernandez, Eglée (Journal of the Spanish Institute for Strategic Studies, 2026)
This article analyzes the strategic communication of the Military Emergency Unit (UME) on Twitter during the forest fires that affected Spain in July and August 2025, one of the most severe episodes in recent decades. The study starts from the premise that institutional communication on social media is a fundamental resource to reinforce transparency, legitimacy, and public trust in contexts of crisis that compromise national security. The corpus of analysis includes 175 tweets published by the official @UMEgob account, collected through scraping and examined using a mixed-methods approach. A descriptive analysis of frequency and engagement was conducted, along with a thematic classification adapted from the literature on crisis communication, and a semantic analysis using the data analysis software Graphext. The results show that UME’s communication strategy was eminently reactive and operational, with peaks of activity coinciding with the most critical moments of the fires. Informative messages about deployments and resources predominated, obtaining the highest levels of citizen interaction. Institutional values and territorial references reinforced the legitimacy of the institution. However, the limited presence of preventive messages reveals a focus centered on immediate response rather than on citizen preparedness.